Comparison of stress in freshman and senior nursing students - Fernanda Carneiro Mussi; Cláudia Geovana da Silva Pires; Luciana Santos Carneiro; Ana Lúcia Siqueira Costa; Fernanda Michelle Santos e Silva Ribeiro; Andréia Ferreira dos Santos
ABSTRACT Objective: To compare stress levels in freshman and senior nursing students. Method: A cross-sectional study was carried out in a public federal university of the state of Bahia, with students who answered questionnaires about sociodemographic variables, academic life, and a scale for assessing stress in nursing students. Chi-square and Fisher's exact tests were applied to analyze the relationship between variables. To assess proportional trends between ordinal variables and groups, a chi-square test for linear trend was applied. The significance level was 5%. Results: One hundred and fifty-four students participated in the study. There was a tendency to higher stress levels among students in the last year compared to those in the first year, in four out of six domains: Performance of Practical Activities (p=0.00), Professional Communication (p=0.00), Environment (p=0.00) and Professional Education (p=0.00). Conclusion: High levels of stress were observed in students taking the last year. There is a need for broader research that includes other years of the course, an institutional reflection on stress factors and the adoption of an institutional policy that favors a better confrontation of stress factors.